2020
DOI: 10.4103/jgid.jgid_58_20
|View full text |Cite
|
Sign up to set email alerts
|

A clinicohistopathological correlation of Hansen's disease in a rural tertiary care hospital of Central India

Abstract: Background: Leprosy is an ancient, chronic granulomatous infectious disease caused by Mycobacterium leprae , principally affecting the skin and peripheral nerves. The clinical manifestations of leprosy are variable and can mimic a variety of other skin diseases. Thus, histopathological examination plays an important role in early diagnosis and management. Aim: The aim was to study the clinicohistopathological correlation of all suspected cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In the studies done by Sinha et al [14] and Srismitha [15] most common age group affected was 31-50 years which was similar to our study whereas in the studies done by Atram et al [16] found majority of cases in age group was 21-40 years.…”
Section: Resultssupporting
confidence: 90%
“…In the studies done by Sinha et al [14] and Srismitha [15] most common age group affected was 31-50 years which was similar to our study whereas in the studies done by Atram et al [16] found majority of cases in age group was 21-40 years.…”
Section: Resultssupporting
confidence: 90%
“…17 Atram et al in 2020 reported 113 (59.8%) males and 76 (42.2%) females. 18 Borderline Tuberculoid (BT) and Borderline Lepromatous (BL) category comprised of most cases in our study, 14 (31.1%), followed by 9 (20.0%) cases in Lepromatous Leprosy (LL). Aarão et al in 2014 also reported 34.0% cases in the Mid Borderline category followed by 32.0% cases in Tuberculoid category.…”
Section: Discussionmentioning
confidence: 62%